A Lightweight Signcryption Method for Perception Layer in Internet-of-Things. (December 2020) - Kumar, Ashish; Saha, Rahul; Alazab, Mamoun; Kumar, Gulshan
Abstract: Internet-of-Things (IoTs) are one of the most promising technologies in the present world. It connects people, processes and things. The increasing number of devices in IoT invoking various security and privacy issues. Authentication is one of them which should be measured at the very first level when a device comes into the network. Many authentication schemes are in use which follow the traditional cryptographic techniques of first-sign-then-encryption. The low performance and high complexity of these techniques also have urged the development of signcryption and lightweight signcryption techniques which are more beneficial for low-powered devices in IoTs. The literature study also provides a scope of improvement in the existing signcryption techniques. With this objectives, in this paper, the work shows a lightweight signcryption scheme for perception layer devices in IoT. It uses PHOTON-256 as a lightweight hash function which makes the proposed scheme less complex and faster. The performance of the scheme has been measured in terms of complexity, cost analysis and energy consumption. AVISPA validation is performed to evaluate security. The analysis of attacks, comparative experimentation and energy consumption confirm the efficiency of the scheme.